2019
DOI: 10.1371/journal.pone.0207967
|View full text |Cite
|
Sign up to set email alerts
|

Lateral ventricle volume trajectories predict response inhibition in older age—A longitudinal brain imaging and machine learning approach

Abstract: Objective In a three-wave 6 yrs longitudinal study we investigated if the expansion of lateral ventricle (LV) volumes (regarded as a proxy for brain tissue loss) predicts third wave performance on a test of response inhibition (RI). Participants and methods Trajectories of left and right lateral ventricle volumes across the three waves were quantified using the longitudinal stream in Freesurfer. All participants ( N = 74;48 females;mean age 66… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 57 publications
1
12
0
Order By: Relevance
“…To construct subject specific trajectories for each measure we used linear mixed effects models 23 , 24 , a class of models able to produce regression models from dependent variables 25 . Our models are based on the one presented in 24 and similar to the ones employed in our previous works 19 , 26 . As the ventricles show quadratic cohort behaviour (Fig.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To construct subject specific trajectories for each measure we used linear mixed effects models 23 , 24 , a class of models able to produce regression models from dependent variables 25 . Our models are based on the one presented in 24 and similar to the ones employed in our previous works 19 , 26 . As the ventricles show quadratic cohort behaviour (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…In a first set of analyses we defined features characterising longitudinal changes in memory function (Rey Auditory Learning Test (RAVLT)) 11 and in a more global measure of cognitive function (ADAS-Cog-13 (ADAS13)) 9 , 17 . Expecting more precise predictions by including information from MRI examinations 15 , 16 , we investigated the add-on effect of including morphometric brain measures associated with memory function (entorhinal cortex and hippocampus 14 ) and a global measure of cognitive function (the volume of the ventricles as a proxy for a global tissue loss 18 ). More specifically, we used a pipeline proposed by Mofrad et al 19 based on a combination of mixed effects and machine learning models for analysis of longitudinal data.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Scahill et al observed an average ventricular volume expansion rate of 0.65 cm 3 /year, which they link to brain atrophy, changes in CSF dynamics, and the distribution of CSF in the ventricular and sulcal spaces ( Scahill et al, 2003 ). While most studies report total ventricular volume changes, Lundervold et al observed a left-right ventricle expansion asymmetry and reported an annual 2.9% increase of the left and 3.1% of the right ventricular volume ( Lundervold et al, 2019 ).…”
Section: Morphological Changes Associated With Healthy Brain Agingmentioning
confidence: 99%
“…There are several factors contributing to this 20 , with one crucial obstacle being that most of these algorithms are constructed using data that are expensive and/or invasive to obtain. Although the inclusion of more invasive biomarkers 21,22 and/or longitudinal data [23][24][25] would increase the predictive power of the algorithms, this information is rarely obtained in an initial clinical examination of a MCI subject. To the best of our knowledge, few studies have aimed at creating classification models based on clinically relevant features, with a study from Grassi and colleagues 26 being an exception.…”
Section: Introductionmentioning
confidence: 99%